The Jews of Algeria and their position on the French occupation - maouchi, amel (The Algerian Historical Journal, 2026)
During the Ottoman era, the Jews of Algeria formed part of the society , and they were coexisted with the rest of the groups, but in 1830 it brought about a great change for them because of the French occupation, and it was for them the beginning of a new era, so they welcomed the French with great joy as liberators and saviors, and soon they assisted the occupation and became his Aid against Muslims. Exposing the position of the Jews towards the occupation is our aim in this historic contribution, and we concluded through it that the Jews of Algeria decided their position from the beginning in favor of the French to preserve their interests.